2015
DOI: 10.1007/s13337-015-0259-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses of genes differentially expressed by high-risk and low-risk human papilloma virus E6 oncoproteins

Abstract: Human papilloma virus is the causative agent for cervical cancer with 99 % of cervical cancer cases containing HPV. The high risk HPV-16, 18 and 31 are the major causative agents. The low risk HPV-6, 11 have been reported to cause penile, laryngeal, bronchogenic and oesophageal cancer. Since E6 oncoprotein is frequently over expressed in cancers, we did gene expression studies to compare between the E6 genes of high-risk (HPV18) or low-risk (HPV11)stably transfected in epithelial cell line EPC-2 or mock transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…Amongst the differentially expressed ESCC genes identified, some hits have been highlighted in previous studies, including MCM4, MMP1, MMP12, SLC22A3 along with members of the CLIC family [25][26][27]. Furthermore, based on the results of the GSEA analysis, p53 pathways along with cell cycle regulation were also de-regulated in ESCC, a finding that had been reported previously [28]. For validating our datasets we chose the CLIC family of genes, not because they represented the most highly over-or under-expressed genes in ESCC.…”
Section: Discussionsupporting
confidence: 69%
“…Amongst the differentially expressed ESCC genes identified, some hits have been highlighted in previous studies, including MCM4, MMP1, MMP12, SLC22A3 along with members of the CLIC family [25][26][27]. Furthermore, based on the results of the GSEA analysis, p53 pathways along with cell cycle regulation were also de-regulated in ESCC, a finding that had been reported previously [28]. For validating our datasets we chose the CLIC family of genes, not because they represented the most highly over-or under-expressed genes in ESCC.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, our data unveil a possible link between LLT1/CLEC2D expression and HPV infection. In line with this, CLEC2D expression was found to be upregulated by HPV E6 oncoprotein [23]. Similarly, it has also been demonstrated that PD-L1 expression is induced by HPV16 E7 oncoprotein, thereby leading to antitumor response inhibition in cervical cancer [24].…”
Section: Discussionsupporting
confidence: 57%
“…Despite the fact that the association between HPV infection and benign as well malignant lesions of the upper respiratory tract has been already well documented, there are still ambiguities of the pathways leading to the malignant transformation of the cells (8,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%